1997
DOI: 10.1124/mol.52.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Is a Muscarinic Antagonist in Cardiac Myocytes

Abstract: SUMMARYWe studied the mechanism of action of methylene blue (Mblue), a putative guanylyl cyclase inhibitor, on the L-type calcium current (I Ca ) and the muscarinic activated K ϩ current (I K,ACh ) in rat ventricular and atrial myocytes, respectively, and on the binding of [3 H]quinuclidinyl benzylate in rat ventricular membranes. Superfusion, but not internal dialysis, with 30 M Mblue antagonized the inhibitory effect of acetylcholine (ACh, 1 M) on ␤-adrenergic stimulation of I Ca with isoprenaline (Iso, 10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…8B), there is now an opportunity to rationalize the binding modes of the thus far uncharacterized ligands that bind to mAChRs. Thus, we calculated the docking results for NSC27366 and for methylene blue, an organic dye that has been shown to be an antagonist at mAChR (Abi-Gerges et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…8B), there is now an opportunity to rationalize the binding modes of the thus far uncharacterized ligands that bind to mAChRs. Thus, we calculated the docking results for NSC27366 and for methylene blue, an organic dye that has been shown to be an antagonist at mAChR (Abi-Gerges et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…However, methylene blue and LY83583 exhibit several non-specific effects, including inhibition of nitric oxide synthase and generation of superoxide anions with accompanying auto-oxidation of NO [15]. In addition, methylene blue appears to act as a muscarinic receptor antagonist [16]. Thus, the literature in this area is contradictory.…”
Section: Introductionmentioning
confidence: 76%
“…It was already reported that some psychotropic drugs with higher concentration ranges inhibited a cardiac type of GIRK channel in an over-expression system of Xenopus oocytes and CHO cells [16,17,28]. Moreover, it was reported that chlorpromazine inhibited the acetylcholine-induced I K.ACh with a threshold of ~30 nM in rat atrial cardiomyocyte [1]. In the present experiments, it was found that antipsychotics and antidepressants inhibited I K.ACh in native cardiac myocytes within or close to clinical plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a couple of antipsychotics and antidepressants inhibited GIRK channel current in an over-expression system [16,17]. Moreover, chlorpromazine inhibited I K.ACh in rat cardiac myocytes [1]. However, influences of most psychotropic drugs on native cardiac myocytes were not fully examined.…”
mentioning
confidence: 99%